2015
DOI: 10.4238/2015.december.16.30
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the TNF-α-308G/A polymorphism and vitiligo risk

Abstract: ABSTRACT. Several case-control studies have been conducted to investigate the association between the tumor necrosis factor-α (TNF-α)-308G/A polymorphism and vitiligo risk. However, the results of these studies are inconsistent; therefore, we attempted to comprehensively evaluate the association between TNF-α-308G/A polymorphism and vitiligo risk via a meta-analysis. Studies reporting the association between TNF-α-308G/A polymorphism and vitiligo risk were retrieved from PubMed and EmBase databases. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There is conflicting evidence regarding the association between TNFA-308(G > A) and vitiligo susceptibility [21,30,[51][52][53][54][55][56][57]. Variations in ethnicity and smaller sample sizes may have contributed to the difficulty in conclusively establishing a genetic association between TNFA-308(G > A) SNP and vitiligo susceptibility risk [58,59]. In light of recent associations between TNFA-308(G > A) SNP and vitiligo susceptibility, meta-analysis should be performed to enhance statistical power and elucidate the exact role of this SNP in vitiligo susceptibility [21,56,60].…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence regarding the association between TNFA-308(G > A) and vitiligo susceptibility [21,30,[51][52][53][54][55][56][57]. Variations in ethnicity and smaller sample sizes may have contributed to the difficulty in conclusively establishing a genetic association between TNFA-308(G > A) SNP and vitiligo susceptibility risk [58,59]. In light of recent associations between TNFA-308(G > A) SNP and vitiligo susceptibility, meta-analysis should be performed to enhance statistical power and elucidate the exact role of this SNP in vitiligo susceptibility [21,56,60].…”
Section: Discussionmentioning
confidence: 99%
“…However, lack of association of -308A with vitiligo in Turkish and Northeastern Mexican ethnic groups was also reported [26, 27]. A meta-analysis by Nie et al [28] and Wu et al [29] showed that the TNF-α -308A variant was not associated with the development of viti­ligo. However, a meta-analysis based on geographical stratification by Lee and Bae [30] revealed that the TNF-α -308G/A polymorphism was significantly associated with vitiligo susceptibility in Middle Eastern populations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genetic predisposition is also reported. Increasing numbers of vitiligo susceptibility genes and candidate genes have been discovered, such as VDR (Maresca et al, ), COMT (Li et al, ), TNF (Nie et al, ), CAT (Liu et al, ), COX2 (Li et al, ), Nrf2 (Guan et al, ), and AHR (Wang et al, ); the details of single nucleotide polymorphisms in vitiligo susceptibility genes are shown in Table . Genetic mutations or polymorphisms may cause congenital defects of melanocyte function or a lack of ability to resist external harmful factors and self‐repair, thereby increasing the risk of individuals developing vitiligo.…”
Section: Discussionmentioning
confidence: 99%